Rasgos anatómicos de la madera de especies comunes de bosque seco en la Reserva Natural Laipuna al sur de Ecuador - Cartuche Peralta, Keyla Mabel (2023)
The dry forests of Ecuador are located in the central and southern part of the western Andes region between 0 – 1 000 m above sea level. Despite their high diversity and the complex dynamics of these forest ecosystems, little is known about their functional traits, especially the anatomical features of the wood, and their adaptation processes in situ in dry forests. Therefore, this study anatomically characterized 22 forest species and determined their basic density at 600 and 1 200 m above sea level. With the help of a Pressler borer, two 5 cm long wood cores were obtained from 8 trees per species. These cores allowed the determination of the basic density of the wood and the quantitative and qualitative anatomical characteristics. Additionally, changes in the variables were determined with principal component analysis and correlation graphs. The results showed that at 600 m above sea level, the species have low density, high moisture content, larger lumen area and vessel diameter, lower vessel density, higher specific conductivity, solitary vessels, and apotracheal and paratracheal parenchyma. Meanwhile, at 1 200 m above sea level, the species have high density, lower moisture content, higher vessel density, smaller lumen area and vessel diameter, lower conductivity, grouped vessels, and rare parenchyma. This study demonstrated that the anatomy of wood varies at different altitudes. These variations are mainly influenced by differences in temperature and relative humidity between sites. This type of research allows understanding the adaptability and resilience of forest species in different climatic conditions, as the anatomical traits of the wood can be biological indicators of the site. Therefore, it is necessary to expand these studies, to contribute to the generation of knowledge of species more resilient to global change. Keywords: Wood anatomy, functional traits, wood basic density, altitude, quantitative and qualitative analysis, deciduous.